Analisis Pengaruh Fluktuasi Harga Emas Terhadap Omset Perum Pegadaian Cabang Cicurug - Rizki Ahmad Fauzi; Siti Nurbijah (STIE Binaniaga, 2007)
The impact of gold’s exchange rate and price fluctuation on the profitability of Cicurug Pawnshop Branch Office. A pawnshop is a non-bank financial institution that was founded on April 1st 1901 during the Dutch Colonialism period. Pawnshop has been chosen for years as an alternative solution to fight against the usury system and usurers. The pawnshop was very important to improve the economical life of Indonesian people at that time. As the time went on, the pawnshop gained more success as can be seen in 1990 when the pawnshop changed its form into a public company where it can make a quick jump to promote its core business. At the moment, the pawnshop is an independent financial institution and organized by professionals with a good management system. Since then pawnshop has been providing multi products and services programs such as Safe and Quick Credit / Kredit Cepat Aman (KCA), Kreasi, Krasida, Krista, Gadai Syariah, Gadai Efek and the like. KCA is based on pawn law form and became the core product of the pawnshop. As we know through the economical development of Indonesia that people prefer to choose gold for his or her own deposits. Gold has some good characteristics, such as it is practical to use as deposit, it is liquid and has good and stable exchange rate and moreover its price increases steadily and continuously from year to year. Amazingly the pawnshop has a good capability to control its loss. This is the reason why the writer intended to make an analysis of how the gold’s exchange rate and price influence the profitability of Cicurug Pawnshop Branch Office. By using statistical computation and comparing t table with t counted it is proved that there is no significant influence of the gold’s rate and price on the profitability of Cicurug pawnshop Branch. This can be seen from t counted that is smaller than t table (t counted 0.391< t table 2.257).